Character sketches from the pages of Scripture, illustrated in the world of nature - Institute in Basic Youth Conflicts ([Oak Brook, Ill.] : The Institute, 1976)
Discusses Christian character traits illustrated in the Bible and nature.
Includes indexes.
Keywords: Christian ethics -- Juvenile literature; Bible -- Juvenile literature; Animals -- Juvenile literature; Zoology -- Miscellanea -- Juvenile literature; Christian life; Bible stories; Animal behavior; Bible; Animals; Christian ethics; Zoology -- Miscellanea; Juvenile works